2018
DOI: 10.5296/ajfa.v9i2.12076
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Capital Structure on the Financial Performance of the Jordanian Industrial Companies Listed on the Amman Stock Exchange for the Period 2012-2015

Abstract: The purpose of this study was to identify the effect of the capital structure as a percentage of total liabilities to total assets on the financial performance of the Jordanian industrial companies listed on the Amman Stock Exchange for the period 2012-2015.The study population included all the Jordanian general industrial companies listed on the Amman Stock Exchange. The sample of the study included 10 industrial companies listed on the Amman Stock Exchange. The linear regression analysis was used to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This implies that the implementation of Target Costing technique does enhance the performance of the firms. The finding of this study is consistent with the outcome of the studies of Alsoboa et al (2015), Imeokparia and Adebisi (2014), Kaneko et al (2013), andHuang, Lai andChun (2012), which report positive effect of target costing implementation on the overall financial performance, return on investment and cost reduction, and strong impact on organizational achievement. Hence, the hypothesis, Ho 2: Target costing has no significant effect on organizational performance of manufacturing firms is not supported.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…This implies that the implementation of Target Costing technique does enhance the performance of the firms. The finding of this study is consistent with the outcome of the studies of Alsoboa et al (2015), Imeokparia and Adebisi (2014), Kaneko et al (2013), andHuang, Lai andChun (2012), which report positive effect of target costing implementation on the overall financial performance, return on investment and cost reduction, and strong impact on organizational achievement. Hence, the hypothesis, Ho 2: Target costing has no significant effect on organizational performance of manufacturing firms is not supported.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…Other research states that the factors that can affect organizational performance are the characteristics of entrepreneurs, implementing best practices and the competitive advantage of an organization(Rahman & Ramli, 2014). In line with these findings(Alsoboa et al, 2015) states that competitive advantage has a significant effect on organizational performance. Furthermore,(Alawadi et al, 2019) found that there is a significant influence between competitive advantage and organizational performance, this is based on the finding that increasing competitive advantage can help organizations assess organizational capabilities and potential, assist in internal and external environmental assessments.…”
mentioning
confidence: 78%
“…SMA usage was measured by requesting respondents to rank the extent to which their firms use a list of 19 SMA techniques on a five-point scale of 1 (not at all) to 5 (very great extent) employing the following question: To what extent does your organization use the following accounting techniques? Immediately following the question, 19 SMA techniques were briefly described (see Guilding and McManus, 2002;Cadez and Guilding, 2008;Cinquini and Tenucci, 2010;Fowzia, 2011;Alsoboa et al, 2015). The scores for the techniques were averaged to develop an index for SMA usage intensity.…”
Section: Sma Usage Intensitymentioning
confidence: 99%